Desenvolvimento de um método tentativo de gerenciamento de fornecedores num ambiente de desenvolvimento simultâneo tridimensional - Nunes, Moema Pereira (Universidade do Vale do Rio do Sinos, 2005)
At the last decades, significant changes occured in different markets raised the degree of competitiveness among the different industrial sectors. At the same time, the evolution of the Logistic allowed the approach of the companies that belong to the Supply Chain. In the search for the reach and maintenance of the competitiveness, many organizations had visualized this approach as a chance to get advantages through the inclusion of suppliers in the process of development of new products and processes This inclusion of suppliers allows the creation of an environment of Three-dimensional Simultaneous Development, in which the product, the process and the supply chain is development at the same time. Despite the benefits of this inclusion being widely divulged, nor all the companies who had carried through this integration had obtained success. Part of the failures can be related with the lack of a mechanism that guide the integration of suppliers in the development of products and processes. Aiming at to f
Keywords: desenvolvimento simultâneo tridimensional; gerenciamento de fornecedores; logística; logistics; supplier management; three-dimensional concurrent engineering; Ciências Sociais Aplicadas